In vitro and in vivo anti-lung cancer properties of leaf ethanolic extract of morinda citrifolia l. - Lim, Swee Ling (2015)
Lung cancer causes 1.4 million deaths and 1.6 million new cases annually, worldwide. The non-small-cell lung cancer (NSCLC) represents 75% – 80% of lung cancer cases. Morinda citrifolia leaves (a common tropical vegetable) scopoletin and epicatechin rich extract (MLE) were assessed for anti-lung cancer effects in vitro on A549 NSCLC cells and in vivo on BALB/c mice. Cell death was assessed by MTT, caspase assays, cell cycle and fluorescence microscopy. The lung cancer was induced by subcutaneously injecting A549 cells into the back of BALB/c mice. The MLE inhibited the proliferation and induced apoptosis in A549 cells (IC50 = 23.47 μg/mL), arrested cancer cell cycle at G0/G1 phases and significantly increased caspase-3/-8 without changing caspase-9 levels. It was not cytotoxic on non-cancerous MRC-5 lung cells even at 100 The orally administered MLE significantly upregulated the proapoptotic P53 genes and downregulated the pro-tumorigenesis genes (BIRC5, JAK2/STAT3/STAT5A) in the tumour tissues. Cancer development is closely associated with inflammation, oxidative stress and uncontrolled cell growth. The effects of the MLE containing scopoletin (2.2%) and epicatechin (3.4%), on inflammation, endogenous antioxidant responses and apoptosisrelated genes expression in lung-cancer induced mice, compared with the anti-cancer drug Erlotinib were investigated. NSCLC-induced BALB/c mice were fed with 150 and 300 mg/kg MLE and compared with Erlotinib (50 mg/kg body-weight) for 21 days. It significantly increased the anti-inflammatory IL4, IL10 and NR3C1 expressions in the lung and hepatic tissues, enhanced the NFE2L2-dependent antioxidant responses against oxidative injuries and elevated the serum neutrophils. It suppressed inflammation and oedema, while up-regulated the endogenous antioxidant responses and apoptosis genes to suppress the metastasized cancers. The MLE significantly increased blood lymphocytes counts, spleen tissues B cells, T cells and natural killer cells, and reduced the epidermal growth factor receptor (EGFR) which is a lung adenocarcinoma biomarker. The MLE also suppressed the cyclooxygenase 2 (COX2) inflammatory markers; and enhanced the tumour suppressor gene (phosphatase and tensin homolog, PTEN). The MLE inhibited the tumour growth cellular genes (transformed mouse 3T3 cell double minute 2 (MDM2), V-raf-leukemia viral oncogene 1 (RAF1), and mechanistic target of rapamycin (MTOR)) mRNA expressions. Cancer development is also related with angiogenesis and metastasis. The antiangiogenesis and anti-metastasis properties of MLE were investigated and compared with Erlotinib. The 300 mg/kg body-weight MLE was 41% more effective than 50 mg/kg body-weight Erlotinib in suppressing the lung tumor growth; down-regulating new tumour-related blood vessel development or angiogenesis-relevant genes (VEGFA; AKT1; BCL2; MAP3K14 and MAPK1) in both the liver and lung tissues. The MLE suppressed lung and liver cancer invasive migration or metastasis via down-regulating angiogenesis biochemical pathways (EGFR, MMP9 and integrin). The 300 mg/kg body-weight MLE significantly (and dose-dependently) suppressed lung tumour growth, more effectively than the 50 mg/kg body-weight Erlotinib treatment for most of the parameters measured. Part of the mechanisms involved enhancing immune responses, suppressing proliferation and interfering with various tumour growth signalling pathways, angiogenesis and metastasis in both the lung and liver tumours.